Effect of catheter-based renal sympathetic denervation on 24-h ambulatory blood pressure in patients with resistant hypertension. (August 2014) - Völz, Sebastian; Andersson, Bert; Manhem, Karin; Haraldsson, Inger; Rundqvist, Bengt
Abstract We investigated the effect of renal denervation on office blood pressure (OBP) and 24-h ambulatory blood pressure (BP) measurement (ABPM) at baseline and 6 months after intervention in 25 consecutive patients with resistant hypertension. Mean baseline 24-h ABPM and OBP were 158/88 mmHg and 169/96 mmHg, respectively. Patients were treated with an average of 4 ± 1 antihypertensive drugs. Among the 22 patients included in data analysis, mean ambulatory systolic and diastolic BP were reduced by 6 mmHg from 158 ± 17 to 152 ± 20 mmHg (p < 0.05) and by 3 mmHg from 88 ± 12 to 85 ± 14 mmHg (p = ns) after 6 months follow-up, respectively. Blood pressure reduction was most pronounced during daytime with a decrease of 9 mmHg from 164 ± 17 to 155 ± 19 (p < 0.05) in systolic (SBP) and 6 mmHg from 94 ± 14 to 88 ± 14 mmHg in diastolic BP (DBP) (p < 0.05). Night-time SBP mmHg and DBP were similar at baseline compared with follow-up. Systolic and diastolic OBP during follow-up were significantly reduced by 17 mmHg from 169 ± 20 to 152 ± 21 (p < 0.05) and by 9 mmHg from 96 ± 16 to 87 ± 13 mmHg (p < 0.05), respectively. These results provide new insight into the effect of renal denervation on ABPM day- and night-time blood pressure profile in comparison with OBP. The decrease in ABPM was identified during daytime registration and was less pronounced compared with reduction of OBP.